ELEKTROFORESIS PROTEIN SERUM PASIEN DENGAN KADAR PROTEIN NORMAL - Tiene Rostini; Coriejati Rita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Serum protein electrophoresis pattern can assist in diagnosis of liver disease, hematological disorders, renal disorders andgastrointestinal disease. Measurement of total protein level in the serum cannot detect any disorders in patient with normal limit ofserum total protein level. The aim of this study; was to evaluate the serum protein electrophoresis pattern in patient with normal limitsof serum protein level. This research was carried out by descriptive retrospective study using the electrophoresis data from patients’medical record at the Clinical Pathology Department, Dr. Hasan Sadikin General Hospital Bandung. The data of serum electrophoresis (bySebia gel electrophoresis) were grouped based on disease or disorders, and confirmed with the diagnosis derived from patient’s medicalrecord. Inclusion criteria of samples if ; the electrophoresis data were available, serum total protein level within normal limits (6.4–8.3mg/dL), and the data of electrophoresis taken from medical record were taken from August 2006 until August 2008. The result foundso far was, there were 240 data of electrophoresis from patients with serum protein level within normal limits (6.4–8.3 mg/dL). theinterpretation of electrophoresis consist of: 1) inflammation (149 patients; 62.2% ; sensitivity 83.7%, specificity 86,5%) 2) Cirrhosis(46 patients ; 19.2% ; sensitivity 87.5% ; specificity 88.4%) 3) Nephritic syndrome (15 patients ; 6.2%; sensitivity 53%; specificity96.9% 4) Monoclonal gammophaty (15 patients(6.2% ; sensitivity 80% ; specificity 98.7%) 5) Normal pattern in 15 patient (6.2%).This study found abnormal serum protein electrophoresis pattern in the condition of inflammation, Cirrhosis, Nephritic Syndrome, andMonoclonal gammophaty. It can be concluded that many disorders could be detected in patient with serum protein level within normallimits such as: inflammation, cirrhosis, nephritis syndrome and monoclonal gammophaty by abnormal electrophoresis pattern